2020
DOI: 10.1177/1049731520915636
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Use Package: Outcomes From a Case Comparison Evaluation

Abstract: The objective was to explore the efficacy of a dual diagnosis resource—the Reasons For Use Package (RFUP)—to build staff capacity to work with service users and explore service user experiences. A two-state case comparison evaluation was conducted employing a mixed methods action research design, utilizing staff and service user surveys combined with focus groups involving staff trained and mentored in use of the RFUP. Results were that both staff and service users responded positively to the RFUP. Staff self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Staff self-reported a statistically significant increase in both knowledge and confidence from pre-to post-training (Myers et al, 2020). The team demonstrated that, through mentoring, the increase in knowledge and confidence can be sustained and enhanced (Myers et al, 2018). Service users reported the RFUP assisted them with reflecting on interactions between their mental health and substance use; this assisted them with goal planning and significantly improved their working relationship with staff (Kroes et al, 2019).…”
Section: Background Of the Reasons For Use Package Development And Tr...mentioning
confidence: 96%
See 3 more Smart Citations
“…Staff self-reported a statistically significant increase in both knowledge and confidence from pre-to post-training (Myers et al, 2020). The team demonstrated that, through mentoring, the increase in knowledge and confidence can be sustained and enhanced (Myers et al, 2018). Service users reported the RFUP assisted them with reflecting on interactions between their mental health and substance use; this assisted them with goal planning and significantly improved their working relationship with staff (Kroes et al, 2019).…”
Section: Background Of the Reasons For Use Package Development And Tr...mentioning
confidence: 96%
“…A literature review in 2015 identified that there was a gap in evidence regarding whether dedicated tools could increase capability of staff (Petrakis et al, 2018). The national trial, commenced in 2015, found that the RFUP has several benefits including: staff confidence and knowledge about dual diagnosis interventions increased; it fits with present State and National mental health and alcohol and other drug (AOD) strategies; and it is recovery-based and user-friendly for a range of health and welfare staff and consumers, and very cost-effective (Myers et al, 2018).…”
Section: Background Of the Reasons For Use Package Development And Tr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the notion that counselors may talk to clients about how their psychedelic experiences, mystical or otherwise, affected their relationship to the givens of existence in a meaningful and therapeutic way may cause hesitation, counselors are reminded that exploring the reasons for and effects of substance use is understood as an integral part of substance use treatment and is not generally considered as putting clients at risk (Aromin, 2016;Myers et al, 2020;Wilson et al, 2020). Given that mystical experiences have been found to be more influential and intense than their non-psychedelic-occasioned counterparts (Yaden et al, 2017), it stands to reason that these experiences should also be considered potentially transformative spiritual experiences as described by Blalock and Holden (2018).…”
Section: Ongoing Psychedelic Integrationmentioning
confidence: 99%